2014
DOI: 10.1016/j.nuclphysb.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Probe anomalous tqγ couplings through single top photoproduction at the LHC

Abstract: In this work we study the constraints on the anomalous tqγ (q=u, c) couplings by photon-produced leading single top production and single top jet associated production through the main reaction pp → pγp → pt → pW(→ ℓν ℓ )b + X and pp → pγp → ptj → pW(→ ℓν ℓ )bj + X assuming a typical LHC multipurpose forward detectors in a model independent effective lagrangian approach. Our results show that: for the typical detector acceptance 0.0015 < ξ 1 < 0.5, 0.1 < ξ 2 < 0.5 and 0.0015 < ξ 3 < 0.15 with a luminosity of 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 162 publications
0
20
0
Order By: Relevance
“…Previous studies using proton-tagging at the LHC for New Physics searches can be found in refs. [3,4,[9][10][11][12][13][14][15][16][17][18][19]. We refer to [20] for a study of light-by-light scattering at the LHC without proton tagging.…”
Section: Jhep02(2015)165 1 Introductionmentioning
confidence: 99%
“…Previous studies using proton-tagging at the LHC for New Physics searches can be found in refs. [3,4,[9][10][11][12][13][14][15][16][17][18][19]. We refer to [20] for a study of light-by-light scattering at the LHC without proton tagging.…”
Section: Jhep02(2015)165 1 Introductionmentioning
confidence: 99%
“…In our case η max = 2.4. Taking into account the cut imposed on the transverse momenta of the muons, |p t | > p t,min , one can transform inequality (32) into the bound on the scattering angle of the muons in the c.m.s of two photons…”
Section: Numerical Analysismentioning
confidence: 99%
“…In this case, SM Wt photoproduction turns to its irreducible background. Moreover, a lot of studies are performed at the γp colliders, i.e., testing anomalous gauge boson couplings [37][38][39][40][41][42] or probing flavour changing neutral currents (FCNC) through Single Top photoproduction [43,44], etc. In cases like these, SM Wt photoproduction turns to be a most important reducible background that needs precise measurement and analysis.…”
Section: Jhep02(2015)064mentioning
confidence: 99%
“…Many phenomenological studies on photon induced processes are summarized here involve: standard model productions [56], supersymmetry [57][58][59][60][61][62], extra dimensions [63][64][65][66], unparticle physics [67], top triangle moose model [68], gauge boson self-interactions [37][38][39][40][41][42][69][70][71][72], neutrino electromagnetic properties [73][74][75], the top quark physics [23,24,36,43,44], dark matter searches [76] and triplet Higgs production [77], etc.…”
Section: Equivalent Photon Approximationmentioning
confidence: 99%